Implementasi Kebijakan Pengelolaan Sampah di Desa Margagiri Kecamatan Bojonegara Kabupaten Serang - M. Farhan Surya Novaldi; Ayuning Budiati; Arenawati (Universitas Serang Raya, 2022)
The most important environmental problem to be solved immediately is the waste problem. This problem is almost every region that experiences it. Likewise, what happened in Margagiri Village, Bojonegara District, Serang Regency. The problem of this research is the efforts made by the margagiri village government to increase community participation in waste management. then find out how the level of community participation in waste management and the Factors Affecting the Community in waste management in Margagiri Village. The research method used by researchers in this study uses field research in the form of qualitative research that has non-statistical properties. In this research procedure, it will later produce descriptive data in thfe form of oral speech and observable behavior from the people (subjects) themselves. The results of the research on waste management in Margagiri Village have not been maximized. There are still obstacles from the Margagiri Village government.Keywords: Implementation Policy, Waste Management, Waste Problem.